Zenons Politeia - Bees, Robert. (Studies on the Interaction of Art, Thought and Power, 2011)
Zeno's Republic, a design of the ideal state consisting of gods and wise citizens, has been controversial since antiquity. The study looks at the controversial topics and tries to come to a new reading of the Republic as the vision of a society where life is lived according to natural law. The provocative call to promiscuity, incest and cannibalism can be explained within the frame of the cosmo-biological system, outlined by the founder of the school. This reading confirms that Stoic ethics with its central theory of oikeiosis is not concerned with the individual's self-discovery as with the cosmos' self-preservation. Attached is a collection of the fragments with German translations. Zenons Politeia, der Entwurf eines idealen Staates bestehend aus Göttern und Weisen, ist seit der Antike umstritten. Die vorliegende Studie behandelt nicht nur die kontrovers diskutierten Argumente, sie will auch zu einer neuen Deutung der Politeia als der Vision einer Gesellschaftsform führen, in der das Leben nach dem Gesetz der Natur verwirklicht ist. Die provokante Forderung nach Promiskuität, Inzest und Kannibalismus erfährt auf diese Weise eine Erklärung innerhalb des kosmo-biologischen Systems, das der Schulgründer geschaffen hat. Damit bestätigt sich die vom Autor jüngst vorgelegte Deutung, daß die stoische Ethik mit der Oikeiosislehre als ihrem Zentrum nicht auf die Selbstentfaltung des Individuums angelegt ist, sondern auf die Selbsterhaltung des Kosmos zielt. Beigegeben ist eine Sammlung der Testimonien mit deutscher Übersetzung.